Decline in pitting corrosion resistance of 316 L stainless steel induced by Cr-depleted layer during tribocorrosion - Zhongwei Wang; Yinchao Wu; Lijie Qiao; Yu Yan (npj Materials Degradation)
Abstract The pitting corrosion resistance of austenite stainless steel was significantly reduced during tribocorrosion: corrosion pits with high density formed far below pitting potential. The aim of this study is to investigate the effects of tribocorrosion on the metastable pitting corrosion behaviour of 316 L stainless steel. The results indicated that the formation of a Cr-depleted layer on nanocrystallized surface (NS) during tribocorrosion played the crucial role in reducing pitting corrosion resistance of the stainless steel. The Cr-depleted layer led to a significant increase in defect density and a reduction in Cr content in the passive film, that increased the number of pitting nucleation sites and weakened the chloride-resistance of the passive film. Further, the initial dissolution of the Cr-depleted layer provided a high cation concentration to sustain pit growth on the NS with high reactivity beneath it. Consequently, metastable pits with high density could initiate and grow at low potentials.